Current and future initiatives for vascular health management in clinical practice - Cameron, James D (Dove Medical Press, 2013)
1. Aortic stiffness is not presently a treatment target but may be useful for substratifying cardiovascular risk in individuals in order to better target the intensity of conventional therapy, and it may be useful in assessing response to treatment. 2. Crosstalk between macro- and microcirculation in hypertension has important implications for pharmacological treatment. An antihypertensive regimen should abolish the vicious cycle between the increased resistance in the microcirculation and the increased stiffness of the larger arteries. Such treatment should be based on drugs with multiple actions on the vascular tree, or on drug combinations that target the various segments of the arterial system. 3. Several blood pressure-independent mechanisms of large artery stiffness exist. Future considerations for clinical understanding of large artery stiffness should involve new drugs and new evaluation methods – with a focus on vascular health, for the initiation of cardiovascular prevention, for newly designed studies for treatment evaluation, and for new studies of drug combinations. 4. Arterial stiffening is a sign of cardiovascular aging and is a major factor affecting the biomechanics of large arteries. Arterial stiffness is an attractive therapeutic target in terms of vascular aging. Healthy lifestyle, physical exercise, and smoking cessation are the most effective ways of preventing and treating early vascular aging. Long-term effects of cardiovascular drugs on arterial stiffness need to be further investigated. 5. The emerging clinical data on the cardio ankle vascular index (CAVI) technique of arterial health assessment is presented, showing that the CAVI is elevated in aging, coronary artery diseases, chronic kidney disease, hypertension, diabetes mellitus, smoking, and stress. The CAVI decreased with the administration of statins, angiotensin II receptor blocking agents, and calcium channel blockers. The CAVI is suggested as an important predictor of cardiovascular diseases. Future development of a clinical understanding of large artery stiffness is important and should include consideration of new drugs and new evaluation methods, with a focus on vascular health aimed at cardiovascular prevention.